Proceedings of the 25th ACM SIGKDD International Conference on Knowledge Discovery &Amp; Data Mining 2019
DOI: 10.1145/3292500.3330777
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Prescribe Interventions for Tuberculosis Patients Using Digital Adherence Data

Abstract: Digital Adherence Technologies (DATs) are an increasingly popular method for verifying patient adherence to many medications. We analyze data from one city served by 99DOTS, a phone-call-based DAT deployed for Tuberculosis (TB) treatment in India where nearly 3 million people are afflicted with the disease each year. The data contains nearly 17,000 patients and 2.1M dose records. We lay the groundwork for learning from this real-world data, including a method for avoiding the effects of unobserved intervention… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…Although studies related to medication adherence predictive models are found in tuberculosis14 and heart failure,15 few studies have been retrieved that established and examined the predictive models in patients with type 2 diabetes mellitus (T2DM), for whom medication adherence is a key factor to treatment outcomes 5 21 22. Kumamaru H et al 23 established a logistic regression model for the prediction of future drug compliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies related to medication adherence predictive models are found in tuberculosis14 and heart failure,15 few studies have been retrieved that established and examined the predictive models in patients with type 2 diabetes mellitus (T2DM), for whom medication adherence is a key factor to treatment outcomes 5 21 22. Kumamaru H et al 23 established a logistic regression model for the prediction of future drug compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to explore the main influencing factors of local patients’ medication compliance and to establish a model that can accurately predict therapeutic compliance in specific regions 12 13. Despite several compliance-related predictive models that have been reported recently in patients with tuberculosis14 and heart failure,15 studies on patients with T2D based on multivariate machine learning algorithms have not been retrieved.…”
Section: Introductionmentioning
confidence: 99%
“…Predicting engagement from user behavior provides the first critical step toward increasing the dosage, frequency and effectiveness of digital interventions. These prediction models can also be used to proactively direct resources toward settings at a higher risk of failure ( Killian et al, 2019 ).…”
Section: The Challenges and Opportunities In Low And Middle Income Comentioning
confidence: 99%
“…It is important to note that Peetluk et al [23] do not classify LR as machine learning in their review as the LR analysis was used as a statistical methodology to understand the relationship between attributes and their prevalence. In the few machine learning studies identified, it was used primarily for predicting treatment completion [39] or unfavourable outcomes [40,41].…”
Section: Related Workmentioning
confidence: 99%